Preparation method of battery diaphragm with wide-temperature-range heat management function

By using electrospinning, vacuum impregnation and in-situ polymerization technologies in the battery separator, a separator with a coaxial spinning fiber embedded microcapsule structure was prepared, which solved the problem that the battery could not effectively adjust the temperature in a wide temperature range, and achieved efficient wide Temperature domain thermal management and performance improvement.

CN119481571APending Publication Date: 2025-02-18WUHAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411414955.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing battery separators cannot effectively adjust the battery temperature in a wide temperature range, resulting in uneven temperature distribution and heat accumulation, and even causing heat out of control.

Method used

Using electrospinning, vacuum impregnation and in-situ polymerization technology, a diaphragm with coaxial spinning fiber embedded microcapsules is prepared. By introducing two materials with large phase change temperature differences, it can coordinate high-temperature melting and low-temperature solidification and heat release. Wide-area temperature control.

Benefits of technology

The battery is efficient and wide temperature domain thermal management is realized, and the battery's performance in a wide temperature domain is improved, which avoids the problem that external thermal management cannot quickly adjust the internal thermal effects of the battery, and at the same time improves the mechanical strength and lithium conduction performance of the diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481571A_ABST
    Figure CN119481571A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a battery diaphragm with a wide-temperature-range heat management function. The preparation method comprises the following steps: dissolving polyacrylonitrile in an organic solvent to serve as a fiber shell precursor solution; dissolving polyethylene glycol and polyvinylidene fluoride in an organic solvent to serve as a fiber inner core precursor solution; respectively pumping the obtained fiber inner core precursor solution and the fiber shell precursor solution into an inner injector and an outer injector, and obtaining a spinning fiber film by adopting an electrostatic spinning technology; placing a microfiltration membrane and the obtained spinning fiber thin film at the bottom of a funnel in sequence, and dropwise adding the phase change microcapsule slurry for vacuum suction filtration; the phase change microcapsule slurry is a suspension containing phase change microcapsule particles, and the particle size is 2-5 [mu] m; washing to remove unfixed phase change microcapsule particles on the surface of the film, and drying; the three technologies of electrostatic spinning, vacuum impregnation and in-situ polymerization are combined, the obtained diaphragm not only has good lithium conduction and mechanical properties at normal temperature, but also has a wide-temperature-range heat management function, and the wide-temperature-range performance of the battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a method for preparing a battery separator material. Background Art

[0002] The rapid development of new energy electric vehicles has put forward higher standards for the operating temperature range of high-performance lithium-ion batteries. Low temperature causes a sharp drop in lithium ion conductivity, and high temperature will also break the electrochemical balance and reduce discharge efficiency. Studies have used phase change materials to perform wide temperature range thermal management of batteries through melting heat storage and solidification heat release. However, phase change thermal management generally acts on the outer surface of the battery and cannot respond to internal thermal effects in a timely manner, resulting in uneven battery temperature distribution, heat accumulation, and even thermal runaway. If phase change materials are introduced into electrochemically inert diaphragms, the battery temperature can be adjusted more sensitively. Among them, organic phase change materials have the potential to be used in diaphragms to regulate battery temperature due to their fixed phase change points, high latent heat and stability. In order to achieve wide-range temperature control, it is usually necessary to introduce two organic materials with a large phase change temperature difference into the diaphragm.

[0003] Electrospinning is widely used in film preparation due to its large porosity, mild preparation conditions and flexible operating space. Studies have used coaxial electrospinning technology to coat phase change materials on fibers to prepare diaphragms to regulate battery temperature. The electrospun diaphragm has large pores, which is conducive to lithium ion conduction at room temperature. However, the mechanical properties of the spun fibers are poor, which may cause a short circuit between the positive and negative electrodes. More importantly, the enthalpy value of coaxial phase change fibers tends to be low; after the introduction of two phase change materials, the latent heat of the diaphragm and the temperature control effect at a specific temperature will be further reduced. Summary of the invention

[0004] In response to the problems of the prior art, the present invention provides a method for preparing a battery separator with a wide temperature range thermal management function, which combines three technologies: electrospinning, vacuum impregnation and in-situ polymerization. The process is simple and has good repeatability, and can achieve large-scale preparation of the separator. The obtained separator not only has good lithium conductivity and mechanical properties at room temperature, but also has a wide temperature range thermal management function, which effectively improves the wide temperature range performance of the battery.

[0005] In order to achieve the above purpose, the technical solutions adopted are as follows:

[0006] A method for preparing a battery separator with a wide temperature range thermal management function comprises the following steps:

[0007] (1) polyacrylonitrile is dissolved in an organic solvent as a fiber shell precursor solution;

[0008] (2) polyethylene glycol and polyvinylidene fluoride are dissolved in an organic solvent as a fiber core precursor solution;

[0009] (3) pumping the obtained fiber core precursor solution and fiber shell precursor solution into inner and outer syringes respectively, and obtaining a spun fiber film by using electrospinning technology;

[0010] (4) placing the microporous filter membrane and the obtained spun fiber film at the bottom of the funnel in turn, and adding the phase change microcapsule slurry dropwise for vacuum filtration; the phase change microcapsule slurry is a suspension containing phase change microcapsule particles with a particle size of 2 to 5 μm.

[0011] (5) Wash and remove the unfixed phase change microcapsule particles on the film surface and dry it.

[0012] According to the above scheme, in step (1), the concentration of polyacrylonitrile is 0.2-0.5 g / mL, the volume is 10 mL, and the organic solvent is dimethylformamide or chloroform.

[0013] According to the above scheme, the polyethylene glycol in step (2) is polyethylene glycol 600 or 400, the organic solvent is dimethylformamide or chloroform, the concentrations of polyethylene glycol and polyvinylidene fluoride are 0.1-0.5 g / mL and 0.01-0.05 g / mL respectively, and the solution volume is 10 mL.

[0014] According to the above scheme, the process parameters used for electrospinning in step (3) are as follows:

[0015] The voltage was 18-20 kV; the distance between the needle and the collector was 5-15 cm; the feed rates inside and outside the syringe were 0.15-0.6 mL / h and 0.5-1.0 mL / h, respectively.

[0016] According to the above scheme, in step (4), the pore size of the microporous filter membrane is 2-5 μm, the concentration of the phase change microcapsule slurry is 0.01-0.1 g / mL, and the slurry volume is 10 mL.

[0017] According to the above scheme, the drying conditions in step (5) are 20-30°C and 10-14 hours.

[0018] According to the above scheme, the method for preparing the phase change microcapsule slurry comprises the following steps:

[0019] S1. Add the formaldehyde solution dropwise into the melamine solution, adjust the pH value to 8.0-9.0 by triethylamine, raise the temperature to 60-80°C and continue stirring for 30-60 minutes to obtain melamine formaldehyde;

[0020] S2. The docosane and styrene-sodium maleic anhydride copolymer solution were mixed, the pH value was adjusted to 4.0-5.0 by citric acid, and the temperature was raised to 50-70 ° C for 30-60 min;

[0021] S3. The melamine formaldehyde obtained in S1 is dripped into the solution obtained in S2 and stirred continuously, and then reacted at 85-95° C. for 2.5-3.5 hours to obtain a phase change microcapsule slurry.

[0022] According to the above scheme, in step S1, the concentration of the melamine solution is 2.826-3.052 g / mL, and the volume is 10 mL; the mass of the formaldehyde solution is 4.66-7.27 g, and the mass fraction is 37%.

[0023] According to the above scheme, in step S2, the styrene-sodium maleic anhydride copolymer solution is 14-56 parts by weight, with a concentration of 4.26wt%; and the docosane is 40-46 parts.

[0024] According to the above scheme, the dropping time in step S3 is 10-30 minutes and the stirring speed is maintained at 500 rpm.

[0025] The present invention firstly adopts coaxial electrospinning technology to prepare polyethylene glycol / polyvinylidene fluoride@polyacrylonitrile (PEG / PVDF@PAN) core-shell structure fiber film, and performs low-temperature thermal management by coagulation heat release of polyethylene glycol 600 at 10°C; then, an in-situ polymerization method is adopted to synthesize docosane@melamine formaldehyde phase change microcapsules, and the melting heat storage of docosane with a melting point of 50°C is used to perform high-temperature thermal management of the battery; finally, a coaxial spinning fiber embedded microcapsule structure film is prepared by vacuum impregnation, and the mechanical and lithium conductivity properties of the diaphragm are optimized by embedding microcapsules.

[0026] The innovation of this invention is to introduce two phase change materials into the diaphragm through coaxial spinning and phase change microcapsules respectively, construct a coaxial spinning embedded microcapsule structure, optimize the porosity and latent heat of the diaphragm, and coordinate high-temperature melting heat storage and low-temperature solidification heat release, so as to achieve wide-range temperature control and high lithium conductivity at room temperature, and improve the wide-temperature performance of the battery. It avoids the problems of external thermal management being unable to quickly adjust the internal thermal effect of the battery, and the low lithium conductivity of the solid electrolyte at room temperature, and provides a new method for improving the wide-temperature performance of lithium batteries.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1) The present invention introduces two materials with a large phase change temperature difference by adopting a hybrid method of coaxial electrospinning and microencapsulation, fully utilizes the space inside and outside the fiber to increase the enthalpy value of the film material, and coordinates high-temperature melting heat storage and low-temperature solidification heat release to achieve efficient wide-temperature range thermal management of the battery.

[0029] 2) The present invention embeds hard microcapsules into the fiber pores, thereby effectively improving the mechanical strength of the diaphragm while ensuring the lithium ion conductivity at room temperature.

[0030] 3) The present invention adopts electrospinning, in-situ polymerization and vacuum impregnation to prepare the diaphragm. The method is simple, the technology is mature, the raw materials are cheap, and a large number of diaphragms can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 : Scanning electron microscope (SEM) and transmission electron microscope (TEM) images of polyethylene glycol / polyvinylidene fluoride@polyacrylonitrile coaxial spinning fibers obtained in Example 1.

[0032] Figure 2 : Scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the docosane@melamine formaldehyde phase change microcapsules obtained in Example 1.

[0033] Figure 3 : Nyquist plot (a) and ionic conductivity (b), EIS curve (c) and mechanical property curve (d) of the products obtained in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.

[0034] Figure 4 : DSC melting-solidification curve of the product obtained in Example 1 (a), temperature-time curves of commercial battery packs coated with the products of Example 1 and Comparative Example 4 during charge and discharge cycles at 30°C (b) and -10°C (c). DETAILED DESCRIPTION

[0035] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0036] The specific embodiment provides a method for preparing a battery separator with a wide temperature range thermal management function:

[0037] (1) polyacrylonitrile is dissolved in an organic solvent as a precursor solution for the fiber shell;

[0038] (2) polyethylene glycol and polyvinylidene fluoride are dissolved in an organic solvent as a precursor solution for the fiber core;

[0039] (3) pumping the inner core and outer shell precursor solutions into the inner and outer syringes respectively for electrospinning;

[0040] (4) dropping formaldehyde into the melamine solution, adjusting the pH value with triethylamine, and continuously stirring to obtain melamine formaldehyde;

[0041] (5) mixing docosane and styrene-sodium maleic anhydride copolymer, and adjusting the pH value by citric acid;

[0042] (6) dropping melamine formaldehyde into the above solution and continuously stirring, and then heating the solution to obtain a phase change microcapsule slurry;

[0043] (7) placing the microporous filter membrane and the spun fiber membrane at the bottom of the funnel in sequence, and adding the phase change microcapsule slurry dropwise for vacuum filtration;

[0044] (8) Wash the unfixed phase change microcapsules on the film surface and dry them.

[0045] Specifically, in step (1), the concentration of 10 mL of polyacrylonitrile is 0.2-0.5 g / mL, and the organic solvent is dimethylformamide or chloroform.

[0046] Specifically, in step (2), the polyethylene glycol is polyethylene glycol 600 or 400, the organic solvent is dimethylformamide or chloroform, the solution volume is 10 mL, and the concentrations of polyethylene glycol and polyvinylidene fluoride are 0.1-0.5 g / mL and 0.01-0.05 g / mL respectively;

[0047] Specifically, the electrospinning conditions in step (3) are: 19 kV voltage, the distance between the needle and the collector is 15 cm, and the feed rates inside and outside the syringe are 0.15-0.6 mL / h and 0.5-1.0 mL / h, respectively.

[0048] Specifically, the reaction conditions of step (4) are: 10 mL of 2.826-3.052 g / mL melamine solution, 4.66-7.27 g of 37% formaldehyde solution, triethylamine to adjust the pH value to 8.0-9.0, reaction temperature to 70° C., and continuous stirring for 30-60 min.

[0049] Specifically, the reaction conditions of step (5) are: 14-56 g of 4.26 wt.% styrene-sodium maleic anhydride copolymer solution, 40-46 g of docosane, citric acid to adjust the pH to 4.0-5.0, reaction temperature 60° C., and continuous stirring at 5000-9000 rpm for 45 min.

[0050] Specifically, in step (6), the dropping time is 10-30 minutes and the stirring speed is maintained at 500 rpm, and then the reaction is continued at 90° C. for 3 hours.

[0051] Specifically, in step (7), the pore size of the microporous filter membrane is 2-5 μm, the concentration of the phase change microcapsule slurry is 0.01-0.1 g / mL, and the amount of the slurry is 10 mL.

[0052] Specifically, the drying condition in step (8) is 12 hours at 25°C.

[0053] Example 1

[0054] A battery separator with a wide temperature range thermal management function, and a preparation method thereof comprises the following steps:

[0055] 1) Weigh 3 g of polyacrylonitrile and dissolve it in 10 mL of dimethylformamide to obtain a precursor solution of a spinning shell;

[0056] 2) Weigh 5 g of polyethylene glycol 600 and 0.4 g of polyvinylidene fluoride and dissolve them in 10 mL of dimethylformamide to obtain a precursor solution for the spinning fiber core;

[0057] 3) pumping the solutions of step 1) and 2) into the outer needle and inner needle of the syringe respectively, and electrospinning was performed under the conditions of 19 kV voltage, 15 cm distance between the needle and the collector, and 0.15 mL / h and 1.0 mL / h feeding rates inside and outside the syringe respectively;

[0058] 4) 2.826 g of melamine powder, 4.66 g of 37% formaldehyde solution and 10 mL of deionized water were uniformly mixed in a three-necked flask, the pH value was adjusted to 8.5 with triethylamine, and the mixture was stirred continuously at 70° C. for 1 hour to obtain melamine formaldehyde;

[0059] 5) 46 g of docosane and 56 g of 4.26 wt.% styrene-sodium maleic anhydride copolymer were mixed, the pH value was adjusted to 4.0 with citric acid, and the mixture was stirred at 60° C. and 9000 rpm for 45 min;

[0060] 6) dropping the solution in 4) into 5) and stirring continuously at 500 rpm for 30 minutes, then raising the temperature to 90° C. and continuing the reaction for 3 hours;

[0061] 7) placing a 5 μm microporous filter membrane and the spun fiber film in 3) at the bottom of the funnel in sequence, and adding 10 mL of microcapsule slurry with a concentration of 0.02 g / mL dropwise for vacuum filtration;

[0062] 8) The unfixed phase change microcapsules on the film surface were washed with deionized water until there was no obvious granularity on the film surface, and dried at 25° C. for 12 hours.

[0063] Figure 1 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the coaxial spinning (product of step 3) obtained in this example are shown in FIG. Figure 1 It can be seen that the fiber has an obvious core-shell structure and the pores of the formed membrane are relatively large.

[0064] Figure 2 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the docosane@melamine formaldehyde phase change microcapsules (product of step 6) obtained in this example are shown in FIG. Figure 2 It can be seen that most of the microcapsules have smooth surfaces and obvious core-shell structures.

[0065] Example 2

[0066] A battery separator with a wide temperature range thermal management function, and a preparation method thereof comprises the following steps:

[0067] 1) Weigh 5 g of polyacrylonitrile and dissolve it in 10 mL of chloroform to obtain a precursor solution of a spinning shell;

[0068] 2) Weigh 5 g of polyethylene glycol 600 and 0.4 g of polyvinylidene fluoride and dissolve them in 10 mL of chloroform to obtain a precursor solution for the fiber core;

[0069] 3) pumping the solutions of step 1) and 2) into the outer needle and inner needle of the syringe respectively, and electrospinning was performed under the conditions of 19 kV voltage, 15 cm distance between the needle and the collector, and 0.15 mL / h and 1.0 mL / h feeding rates inside and outside the syringe respectively;

[0070] 4) 2.826 g of melamine powder, 4.66 g of 37% formaldehyde solution and 10 mL of deionized water were uniformly mixed in a three-necked flask, the pH value was adjusted to 8.5 with triethylamine, and the mixture was stirred continuously at 70° C. for 1 hour to obtain melamine formaldehyde;

[0071] 5) 46 g of docosane and 56 g of 4.26 wt.% styrene-sodium maleic anhydride copolymer were mixed, the pH value was adjusted to 4.0 with citric acid, and the mixture was stirred at 60° C. and 9000 rpm for 45 min;

[0072] 6) dropping the solution in 4) into 5) and stirring continuously at 500 rpm for 30 minutes, then raising the temperature to 90° C. and continuing the reaction for 3 hours;

[0073] 7) placing a 5 μm microporous filter membrane and the spun fiber film in 3) at the bottom of the funnel in sequence, and adding 10 mL of microcapsule slurry with a concentration of 0.02 g / mL dropwise for vacuum filtration;

[0074] 8) The unfixed phase change microcapsules on the film surface were washed with deionized water until there was no obvious granularity on the film surface, and dried at 25° C. for 12 hours.

[0075] Increasing the proportion of polyacrylonitrile in coaxial spinning can better form a core-shell structure and effectively prevent polyethylene glycol leakage, but it also reduces the spinning enthalpy.

[0076] Example 3

[0077] A battery separator with a wide temperature range thermal management function, and a preparation method thereof comprises the following steps:

[0078] 1) Weigh 3 g of polyacrylonitrile and dissolve it in 10 mL of dimethylformamide to obtain a precursor solution of a spinning shell;

[0079] 2) Weigh 5 g of polyethylene glycol 400 and 0.5 g of polyvinylidene fluoride and dissolve them in 10 mL of dimethylformamide to obtain a precursor solution of the fiber core;

[0080] 3) pumping the solutions of step 1) and 2) into the outer needle and inner needle of the syringe respectively, and electrospinning was performed under the conditions of 19 kV voltage, 15 cm distance between the needle and the collector, and 0.15 mL / h and 1.0 mL / h feeding rates inside and outside the syringe respectively;

[0081] 4) 2.826 g of melamine powder, 4.66 g of 37% formaldehyde solution and 10 mL of deionized water were uniformly mixed in a three-necked flask, the pH value was adjusted to 8.5 with triethylamine, and the mixture was stirred continuously at 70° C. for 1 hour to obtain melamine formaldehyde;

[0082] 5) 46 g of docosane and 56 g of 4.26 wt.% styrene-sodium maleic anhydride copolymer were mixed, the pH value was adjusted to 4.0 with citric acid, and the mixture was stirred at 60° C. and 9000 rpm for 45 min;

[0083] 6) dropping the solution in 4) into 5) and stirring continuously at 500 rpm for 30 minutes, then raising the temperature to 90° C. and continuing the reaction for 3 hours;

[0084] 7) placing a 5 μm microporous filter membrane and the spun fiber film in 3) at the bottom of the funnel in sequence, and adding 10 mL of microcapsule slurry with a concentration of 0.02 g / mL dropwise for vacuum filtration;

[0085] 8) The unfixed phase change microcapsules on the film surface were washed with deionized water until there was no obvious granularity on the film surface, and dried at 25° C. for 12 hours.

[0086] By using PEG400 (0°C) with a lower freezing point instead of PEG600 (8°C), the film can release heat at a lower temperature, but the battery performance will decrease below 10°C and needs to be heated to improve performance.

[0087] Example 4

[0088] A battery separator with a wide temperature range thermal management function, and a preparation method thereof comprises the following steps:

[0089] 1) Weigh 3 g of polyacrylonitrile and dissolve it in 10 mL of chloroform to obtain a precursor solution of a spinning fiber shell;

[0090] 2) Weigh 5 g of polyethylene glycol 600 and 0.5 g of polyvinylidene fluoride and dissolve them in 10 mL of chloroform to obtain a precursor solution of the fiber core;

[0091] 3) pumping the solutions of step 1) and 2) into the outer needle and inner needle of the syringe respectively, and electrospinning was performed under the conditions of 18 kV voltage, 15 cm distance between the needle and the collector, and 0.15 mL / h and 0.5 mL / h feeding rates inside and outside the syringe respectively;

[0092] 4) 2.826 g of melamine powder, 4.66 g of 37% formaldehyde solution and 10 mL of deionized water were uniformly mixed in a three-necked flask, the pH value was adjusted to 8.5 with triethylamine, and the mixture was stirred continuously at 70° C. for 1 hour to obtain melamine formaldehyde;

[0093] 5) 46 g of docosane and 56 g of 4.26 wt.% styrene-sodium maleic anhydride copolymer were mixed, the pH value was adjusted to 4.0 with citric acid, and the mixture was stirred at 60° C. and 9000 rpm for 45 min;

[0094] 6) dropping the solution in 4) into 5) and stirring continuously at 500 rpm for 30 minutes, then raising the temperature to 90° C. and continuing the reaction for 3 hours;

[0095] 7) placing a 5 μm microporous filter membrane and the spun fiber film in 3) at the bottom of the funnel in sequence, and adding 10 mL of microcapsule slurry with a concentration of 0.02 g / mL dropwise for vacuum filtration;

[0096] 8) The unfixed phase change microcapsules on the film surface were washed with deionized water until there was no obvious granularity on the film surface, and dried at 25° C. for 12 hours.

[0097] The coaxial electrospinning shell adopts a low feed rate, which can also effectively increase the spinning enthalpy value, but at the same time, the electrospinning voltage needs to be reduced to ensure the stability of the fiber structure.

[0098] Example 5

[0099] A battery separator with a wide temperature range thermal management function, and a preparation method thereof comprises the following steps:

[0100] 1) Weigh 3 g of polyacrylonitrile and dissolve it in 10 mL of dimethylformamide to obtain a precursor solution of a spinning shell;

[0101] 2) Weigh 5 g of polyethylene glycol 600 and 0.4 g of polyvinylidene fluoride and dissolve them in 10 mL of dimethylformamide to obtain a precursor solution for the spinning fiber core;

[0102] 3) pumping the solutions of step 1) and 2) into the outer needle and inner needle of the syringe respectively, and electrospinning was performed under the conditions of 19 kV voltage, 15 cm distance between the needle and the collector, and 0.15 mL / h and 1.0 mL / h feeding rates inside and outside the syringe respectively;

[0103] 4) 2.826 g of melamine powder, 4.66 g of 37% formaldehyde solution and 10 mL of deionized water were uniformly mixed in a three-necked flask, the pH value was adjusted to 8.5 with triethylamine, and the mixture was stirred continuously at 70° C. for 1 hour to obtain melamine formaldehyde;

[0104] 5) 30 g of docosane and 56 g of 4.26 wt.% styrene-sodium maleic anhydride copolymer were mixed, the pH value was adjusted to 4.0 with citric acid, and the mixture was stirred at 60° C. and 9000 rpm for 45 min;

[0105] 6) dropping the solution in 4) into 5) and stirring continuously at 500 rpm for 30 minutes, then raising the temperature to 90° C. and continuing the reaction for 3 hours;

[0106] 7) placing a 5 μm microporous filter membrane and the spun fiber film in 3) at the bottom of the funnel in sequence, and adding 10 mL of microcapsule slurry with a concentration of 0.02 g / mL dropwise for vacuum filtration;

[0107] 8) The unfixed phase change microcapsules on the film surface were washed with deionized water until there was no obvious granularity on the film surface, and dried at 25° C. for 12 hours.

[0108] Reducing the docosane content can form microcapsules with more stable structures, but it will also reduce the enthalpy of the microcapsules.

[0109] Example 6

[0110] A battery separator with a wide temperature range thermal management function, and a preparation method thereof comprises the following steps:

[0111] 1) Weigh 3 g of polyacrylonitrile and dissolve it in 10 mL of dimethylformamide to obtain a precursor solution of a spinning shell;

[0112] 2) Weigh 5 g of polyethylene glycol 600 and 0.4 g of polyvinylidene fluoride and dissolve them in 10 mL of dimethylformamide to obtain a precursor solution for the spinning fiber core;

[0113] 3) pumping the solutions of step 1) and 2) into the outer needle and inner needle of the syringe respectively, and electrospinning was performed under the conditions of 19 kV voltage, 15 cm distance between the needle and the collector, and 0.15 mL / h and 1.0 mL / h feeding rates inside and outside the syringe respectively;

[0114] 4) 2.826 g of melamine powder, 4.66 g of 37% formaldehyde solution and 10 mL of deionized water were uniformly mixed in a three-necked flask, the pH value was adjusted to 8.5 with triethylamine, and the mixture was stirred continuously at 70° C. for 1 hour to obtain melamine formaldehyde;

[0115] 5) 46 g of docosane and 56 g of 4.26 wt.% styrene-sodium maleic anhydride copolymer were mixed, the pH value was adjusted to 4.0 with citric acid, and the mixture was stirred at 60° C. and 9000 rpm for 45 min;

[0116] 6) dropping the solution in 4) into 5) and stirring continuously at 500 rpm for 30 minutes, then raising the temperature to 90° C. and continuing the reaction for 3 hours;

[0117] 7) placing a 5 μm microporous filter membrane and the spun fiber film in 3) at the bottom of the funnel in sequence, and adding 10 mL of microcapsule slurry with a concentration of 0.1 g / mL dropwise for vacuum filtration;

[0118] 8) The unfixed phase change microcapsules on the film surface were washed with deionized water until there was no obvious granularity on the film surface, and dried at 25° C. for 12 hours.

[0119] By adding high concentration of microcapsule slurry during vacuum filtration, the mechanical properties of the formed film can be greatly improved, but the porosity will decrease, which will affect the lithium conductivity at room temperature.

[0120] Comparative Example 1

[0121] This comparative example is a coaxial spun fiber embedded microcapsule structure membrane with different phase change microcapsule contents. The specific preparation method is the same as that of Example 1, except that the concentration of the microcapsule slurry in step 7 is adjusted to 0 g / mL.

[0122] Comparative Example 2

[0123] This comparative example is a coaxial spun fiber embedded microcapsule structure membrane with different phase change microcapsule contents. The specific preparation method is the same as that of Example 1, except that the concentration of the microcapsule slurry in step 7 is adjusted to 0.05 g / mL.

[0124] Comparative Example 3

[0125] This comparative example is a commercial polypropylene diaphragm.

[0126] Comparative Example 4

[0127] This comparative example is a polyacrylonitrile diaphragm without phase change material.

[0128] Application Examples

[0129] The "coaxial spun fiber embedded microcapsule" diaphragm needs to have both high performance at room temperature and thermal management function over a wide temperature range. Considering that adjusting the microcapsule content will change the lithium conductivity and mechanical strength of the diaphragm, and thus affect the room temperature performance of the diaphragm, the room temperature lithium conductivity and mechanical properties of the diaphragm are first studied by adjusting the microcapsule content, and the room temperature lithium ion conductivity and interface impedance are measured and calculated using an electrochemical workstation, and the mechanical properties of the diaphragm are measured using a universal tester. After determining the microcapsule ratio that achieves the optimal room temperature performance, a differential scanning calorimeter is used to study the phase change enthalpy of the film, and the coaxial spun fiber embedded microcapsule structure diaphragm and the polyacrylonitrile film without phase change material are respectively coated on the outside of commercial batteries, and the temperature change curves of the battery charging and discharging under high and low temperature environments are studied, preliminarily exploring the high / low temperature thermal management performance of the experimental diaphragm.

[0130] Figure 3 The Nyquist plot, ionic conductivity, EIS curve and mechanical property curve of the products obtained in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in the figure. It is shown that embedding an appropriate amount of microcapsules can improve ionic conductivity, reduce interfacial impedance and enhance mechanical strength, thereby helping to improve the room temperature performance of the battery. The diaphragm obtained by the present invention can obtain the highest lithium conductivity and mechanical strength, as well as the lowest interfacial impedance when the microcapsule concentration is 0.02g / mL. Therefore, the optimal concentration of microcapsules is set to 0.02g / mL in the following study.

[0131] Figure 4 The melting-solidification curve of the coaxial spun fiber embedded microcapsule film obtained in Example 1, the temperature-time curve of the commercial battery pack coated with the diaphragm in Example 1 and the polyacrylonitrile film without phase change material in Comparative Example 4 when the charge and discharge cycle is carried out at 30°C and -10°C. The figure shows that the melting and solidification enthalpies of the phase change diaphragm obtained by the present invention at 45°C and 10°C are 70J / g and 60J / g, respectively, which are higher than the enthalpy values ​​obtained by using a single phase change material in many literatures, indicating that the hybrid structure can effectively increase the latent heat of the diaphragm. The battery pack was coated with the film of the present invention and the polyacrylonitrile film without phase change material, respectively, and the charge and discharge cycle was carried out at 30°C. The lower temperature of the film of the present invention indicates that it can cool the high-temperature battery by storing the heat generated by the battery. On the other hand, the battery is charged and discharged in an environment of -10°C, and is restarted after a period of suspension. The film of the present invention can not only increase the minimum temperature of the battery when it is suspended, but also help the cold start process of the battery. In summary, the film of the present invention has the potential to control the temperature of the battery over a wide range.

[0132] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.

Claims

1. A method for preparing a battery separator with a wide temperature range thermal management function, characterized in that The steps include: (1) polyacrylonitrile is dissolved in an organic solvent as a fiber shell precursor solution; (2) polyethylene glycol and polyvinylidene fluoride are dissolved in an organic solvent as a fiber core precursor solution; (3) pumping the obtained fiber core precursor solution and fiber shell precursor solution into inner and outer syringes respectively, and obtaining a spun fiber film by using electrospinning technology; (4) placing the microporous filter membrane and the obtained spun fiber film at the bottom of the funnel in sequence, and adding the phase change microcapsule slurry dropwise for vacuum filtration; the phase change microcapsule slurry is a suspension containing phase change microcapsule particles, and the particle size is 2 to 5 μm; (5) Wash and remove the unfixed phase change microcapsule particles on the film surface and dry it.

2. The method for preparing a battery separator having a wide temperature range thermal management function as claimed in claim 1, characterized in that In step (1), the concentration of polyacrylonitrile is 0.2-0.5 g / mL, and the organic solvent is dimethylformamide or chloroform.

3. The method for preparing a battery separator having a wide temperature range thermal management function as claimed in claim 1, characterized in that In step (2), the polyethylene glycol is polyethylene glycol 600 or 400, the organic solvent is dimethylformamide or chloroform, and the concentrations of polyethylene glycol and polyvinylidene fluoride are 0.1-0.5 g / mL and 0.01-0.05 g / mL, respectively.

4. The method for preparing a battery separator having a wide temperature range thermal management function according to claim 1, characterized in that The process parameters used for electrospinning in step (3) are as follows: The voltage was 18-20 kV; the distance between the needle and the collector was 5-15 cm; the feed rates inside and outside the syringe were 0.15-0.6 mL / h and 0.5-1.0 mL / h, respectively.

5. The method for preparing a battery separator having a wide temperature range thermal management function as claimed in claim 1, characterized in that In step (4), the pore size of the microporous filter membrane is 2-5 μm, the concentration of the phase change microcapsule slurry is 0.01-0.1 g / mL, and the slurry volume is 10 mL.

6. The method for preparing a battery separator having a wide temperature range thermal management function as claimed in claim 1, characterized in that The drying conditions in step (5) are 20-30° C. and 10-14 hours.

7. The method for preparing a battery separator having a wide temperature range thermal management function as claimed in claim 1, characterized in that The preparation method of the phase change microcapsule slurry comprises the following steps: S1. Add the formaldehyde solution dropwise into the melamine solution, adjust the pH value to 8.0-9.0 by triethylamine, raise the temperature to 60-80°C and continue stirring for 30-60 minutes to obtain melamine formaldehyde; S2. The docosane and styrene-sodium maleic anhydride copolymer solution were mixed, the pH value was adjusted to 4.0-5.0 by citric acid, and the temperature was raised to 50-70 ° C for 30-60 min; S3. The melamine formaldehyde obtained in S1 is dripped into the solution obtained in S2 and stirred continuously, and then reacted at 85-95° C. for 2.5-3.5 hours to obtain a phase change microcapsule slurry.

8. The method for preparing a battery separator having a wide temperature range thermal management function as claimed in claim 7, characterized in that In step S1, the concentration of the melamine solution is 2.826-3.052 g / mL, and the volume is 10 mL; the mass of the formaldehyde solution is 4.66-7.27 g, and the mass fraction is 37%.

9. The method for preparing a battery separator having a wide temperature range thermal management function as claimed in claim 7, characterized in that In step S2, the styrene-sodium maleic anhydride copolymer solution is 14-56 parts by weight, with a concentration of 4.26wt%; and the docosane is 40-46 parts.

10. The method for preparing a battery separator having a wide temperature range thermal management function as claimed in claim 7, characterized in that The dropping time in step S3 is 10-30 minutes and the stirring speed is maintained at 500 rpm.